Factors associated with extravasation severity in Thai patients receiving noncytotoxic intravenous infusions: An observational study - Thitiporn Pathomjaruwat; Borwarnluck Thongthawee; Padcha Pongcharoen; Charturong Tantibundhit (Belitung Nursing Journal, 2026)
Background: Extravasation is a serious complication of peripheral intravenous (PIV) therapy. It has been linked to mechanical disruption of a PIV line due to inappropriate site selection or securement, and to the pH, concentration, and cytotoxic properties of the infused solution or drug. However, evidence on extravasation in patients receiving noncytotoxic drugs remains limited. Understanding the causes and risk factors in this population is essential for prevention, early detection, and the development of interventions. Objective: To examine demographic and clinical factors associated with extravasation severity in adult Thai patients receiving noncytotoxic drug PIV therapy. Methods: This observational study included 193 participants at high risk of extravasation during PIV therapy. They were recruited from four tertiary hospitals in four regions of Thailand between December 2019 and December 2023 using purposive sampling. Extravasation severity was assessed using an artificial deep neural network for automated screening of skin images via a smartphone application, with confirmation by a dermatologist. Demographic, clinical, and medical data were collected using standardized forms and analyzed with descriptive statistics and Spearman’s rank correlation coefficient. Results: Extravasation was mostly mild (47.67%), followed by moderate (31.09%) and severe (21.24%). Extravasation severity was strongly and negatively correlated with drug pH (r = −0.532; p < 0.01), moderately with concentration (r = 0.411), and methods of drug administration (r = 0.327) (p < 0.01). History of IV insertion showed a mild correlation with severity (r = 0.145; p < 0.05) but not with comorbidities, infusion duration, or catheter size. Conclusion: The results highlight the importance of drug administration, especially the pH and type of drug, concentration, and route of administration, which play a critical role in reducing extravasation, thereby improving PIV therapy outcomes. Nurses play a role in preventing and managing extravasation by controlling the drug’s pH and concentration, carefully monitoring early signs, and promptly initiating interventions.